Metabolic and biomechanical variables of two incline conditions during distance running - Klein, R. M.; Potteiger, J. A.; Zebas, C. J. (Medicine & Science in Sports & Exercise, 1997)
The purpose of this experiment was to examine the effects of an incline during distance running on selected metabolic and biomechanical variables. Six (4 males, 2 females) trained distance runners (age 27.2 +/- 7.8 yr; VO2max 63.7 +/- 7.5 mL x kg-1 x min-1) performed three 35-min runs at speeds corresponding to each individual's anaerobic threshold. The first run (Control) was performed at 0% grade. The remaining two runs were randomly assigned and included a 5% incline during min 5-15 (Run A) or 20-30 (Run B). Heart rate via telemetry (HR), and oxygen consumption (VO2), minute ventilation (VE), RER, and tidal volume (TV) were measured by indirect calorimetry. High speed videography was used to measure time in support phase, time in swing phase, step length, trunk lean, vertical oscillation of the hip, knee flexion in support, shank angle during toe-off, and ankle flexion at heel strike during the runs. Significant increases (P < or = 0.05) were found during the incline conditions of Run A for VO2 (+18%) HR (+11%), VE (+24%), and RER (+8%) and Run B for VO2 (+19%) HR (+10%), and VE (+25%) compared with the Control. No significant differences (P > 0.05) were noted between Run A and Run B during incline running in the physiological variables. No significant differences (P > 0.05) were observed in any of the biomechanical variables among the runs. These data indicate that the energy expenditure required during incline running is the same regardless of incline location during a 35-min run, and running mechanics are not significantly altered during a 5% incline lasting 10 min. In addition, following a 5% incline for 10 min, runners experience no significant physiological or biomechanical changes during subsequent level running at anaerobic threshold pace.